Sensitivity to implant materials in patients with total knee arthroplasties - Granchi, Donatella; Cenni, Elisabetta; Tigani, Domenico; Trisolino, Giovanni; Baldini, Nicola; Giunti, Armando (Biomaterials, 2008)
Materials used for total knee arthroplasty (TKA), may elicit an immune response whose role in the outcome of the arthroplasty is still unclear. The aim of this study was to evaluate the frequency of sensitization in patients who had undergone TKA, and the clinical impact of this event on the outcome of the implant. Ninety-four subjects were recruited, including 20 patients who had not yet undergone arthroplasty, 27 individuals who had a well-functioning TKA, and 47 patients with loosening of TKA components. Sensitization was detected by using patch testing including haptens representative of cobalt-based alloys (CoCrMo), titanium-based alloys (TiAlV), and bone cements. The frequency of positive skin reactions to metals increased significantly after TKA, either stable or loosened (No Implant 20%; Stable TKA 48.1%, p = 0.05; Loosened TKA 59.6%, p = 0.001, respectively). We found a higher frequency of positive patch testing to vanadium in patients who had a Stable TKA with at least one TiAlV component (39.1%, p = 0.01). The medical history for metal allergy seems to be a risk factor, because the TKA failure was fourfold more likely in patients who had symptoms of metal hypersensitivity before TKA. The prognostic value was supported by survival analysis, because in these individuals the outcome of the implant was negatively influenced (the logrank test Chi square 5.1, p = 0.02). This study confirms that in patients with a TKA the frequency of positive patch testing is higher than in the normal population, although no predictive value is attributable to the sensitization because patch testing was not able to discriminate between stable and loose implants. On the contrary, the presence of symptoms of metal allergy before implantation should be taken into account as a potential risk factor for TKA failure.